Collaborative Knowledge Creation as a Driver of Business Sustainability through Proactiveness and Agility in Beauty Brands - Aurelia Sugita Tjandra; Christina Yanita Setyawati (ITScience (Information Technology and Science), 2024)
In the current dynamic and competitive era, local beauty industry companies are faced with tough challenges. Many local brands have emerged to meet the increasing needs and ever-growing expectations of consumers. To ensure business sustainability, organizations need to accept collaboration knowledge as the key to success. This study aims to explain the influence of collaborative knowledge creation towards business sustainability through e-business proactiveness and organizational agility on local beauty brands. This research involves shop owners who sell brand local beauties as a population, with a sample of 138 respondents. Data collection was carried out through online questionnaires using Google Forms media. This research has tested the coefficient of determination, standard deviation test, and reliability test of the data with Cronbach alpha. Data were analyzed using quantitative methods, non-probability sampling, and purposive sampling. Data analysis was carried out using SEM (Structural Equation Modeling) techniques assisted by software SmartPLS 4.0. The research results show that collaborative knowledge creation has a significant positive effect on business sustainability, e-business proactiveness has a significant positive effect on business sustainability, and organizational agility has a significant positive effect on business sustainability. Furthermore, e-business proactiveness and organizational agility partially mediate the relationship between collaborative knowledge creation and business sustainability.